Low-Impact Architectural Design on Contoured Sites: Minimizing Cut-and-Fill for Environmental and Mental Wellness - Abizhar Pradana; Febrione Putri Rakhmanty (ICEETE Conference Series, 2026)
Mountainous sites are increasingly sought after for nature-based wellness tourism, yet their steep, contoured terrain is conventionally treated as an obstacle to be flattened through extensive cut-and-fill earthwork before a resort can be built. This practice increases erosion risk, disrupts natural drainage, and destroys the very topographic and vegetative character that gives such sites their restorative value. This study examines how a contour-following, low-impact design strategy can minimize cut-and-fill intervention while strengthening the nature-based healing quality of a resort, using a proposed Resort Nature-Based Healing in Tawangmangu, Karanganyar Regency, Central Java, Indonesia, as a case. A combination of qualitative, comparative, and quantitative methods was applied, comprising field observation, semi-structured interviews, a visitor-needs questionnaire (n = 48), precedent study, weighted-criteria site selection, and contour (cut-and-fill) analysis. The results show that a cluster-linear massing pattern combined with a terracing strategy, oriented along the natural contour lines, confines earthwork to two limited zones of the 22,415 m² site, while the remaining area retains its original topography and vegetation. This produced stable, code-compliant building platforms, reduced surface-runoff velocity, preserved existing trees, and generated a stepped sequence of semi-private terraces consistent with attention-restoration and nature-based healing principles. The study concludes that contour-following, low-impact site planning reconciles environmental sustainability with mental-wellness-oriented tourism design on sloping terrain and offers a replicable framework for other mountainous wellness-tourism destinations.